The impact of training on discipline outcomes in school-based policing. Issue 3 (15th August 2016) - Martinez-Prather, Kathy E.; McKenna, Joseph M.; Bowman, Scott W.
Abstract : Purpose: The purpose of this paper is to examine the availability of training for police officers working in a school setting and to assess the relationship between training and the types of discipline school-based law enforcement (SBLE) officers most commonly administer to students. Design/methodology/approach: Semi-structured interviews were conducted with SBLE officers in Texas over a six month period. Findings: The findings suggests that almost 40 percent of SBLE officers have not received any specialized training in school policing and more than half report the need for more specialized training to improve job performance. The findings also suggest a relationship between training and the type of disciplinary response SBLE officers provide in schools. Originality/value: The placement of law enforcement officers in schools serves to preserve campuses as safe and secure learning environments; however, it is also viewed as a catalyst for criminalizing student misconduct, often referred to as the school-to-prison pipeline. Although much of the existing literature on SBLE is focussed on its nexus with the school-to-prison pipeline, there remains a lack of investigation into the training SBLE officers receive and how this potentially impacts discipline outcomes in schools.